(untitled) - Jackson, Peter (Cambridge, 1999)
The Delhi Sultanate was the first Islamic state to be established in India. This book traces its history from 1210 to its demise at the sack of Delhi in 1400. While the focus is on military and political affairs, the book also explores the Sultans' relations with their non-Muslim subjects. As a first comprehensive treatment of the period, the book will make a significant contribution to medieval Indo-Muslim history. Students of Islamic and Indian history, and interested general readers, will find it a valuable resource.
Keywords: Delhi (Sultanate),Delhi (Vương quốc Hồi giáo); History,Lịch sử